HIV co‐infection accelerates decay of humoral responses in spontaneous resolvers of HCV infection. Issue 10 (12th February 2014) - Liu, Y.; Shen, T.; Zhang, C.; Long, L.; Duan, Z.; Lu, F.
Summary Acute hepatitis C virus (HCV) infection is primarily followed by chronic infection, while spontaneous recovery of HCV infection (SR‐HCV) occurs in a minority of those infected. Identification of SR‐HCV clinically depends on two combined indicators, persistently undetectable peripheral HCV RNA and positivity for anti‐HCV. However, the characteristics of dynamic variation in anti‐HCV antibodies in SR‐HCV, especially in those patients co‐infected with HIV, are still undefined. In this study, a cohort of patients infected with HCV through commercial blood collection practices was studied. We found that the annual decreasing rate of anti‐HCV presented a gradually accelerated process in HCV resolvers. However, the variation in the decline of anti‐HCV presented a slowly accelerated process within the early decrease stage and a gradually decelerated process within the latter decrease stage. In addition, we deduced that it expended approximately 16 years from natural HCV recovery to undetectable peripheral anti‐HCV in HCV resolvers co‐infected with HIV, while this time was estimated to be 20 years in SR‐HCV without HIV co‐infection. Our data indicated that the decay of anti‐HCV was accelerated by HIV‐related impairment of immune function. The prevalence of HCV infection may be severely underestimated in this large‐scale retrospective epidemiologic investigation in an HIV‐infected population.